Improving Hadith Memorization Ability through Movement Methods for 5-6 Year Old Children at RA Infarul Ghoy - Ida Kartika Afiati; Hikmah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the ability to memorize hadith in children aged 5-6 years through the application of the movement method at RA Infarul Ghoy, Tenggerejo Village, Kedungpring District, Lamongan Regency. The background of this study is based on the low ability of students to memorize hadith, which is caused by the use of learning methods that are less varied and not in accordance with the characteristics of early childhood development. The movement method was chosen because it is in accordance with the learning style of children who tend to be kinesthetic, active, and like fun physical activities. This study is a Classroom Action Research (CAR) which is carried out in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The subjects of this study were 15 children in group B. Data collection techniques were carried out through observation, documentation, and assessment of memorization results. The results of the study showed a significant increase in the ability to memorize hadith after the application of the movement method. In the pre-action, only 26% of children were able to memorize hadith well. After cycle I, it increased to 60%, and in cycle II it reached 86%. This improvement shows that the movement method is effective in helping children understand and remember the contents of the hadith more easily and enjoyably. Thus, it can be concluded that the movement method is able to improve the ability to memorize hadith in early childhood and is worthy of being applied as an innovative learning alternative in early childhood education institutions.